Left ventricular reverse remodelling predicts long‐term outcomes in patients with functional mitral regurgitation undergoing MitraClip therapy: results from a multicentre registry. (13th December 2018) - Adamo, Marianna; Godino, Cosmo; Giannini, Cristina; Scotti, Andrea; Liga, Riccardo; Curello, Salvatore; Fiorina, Claudia; Chiari, Ermanna; Chizzola, Giuliano; Abbenante, Alessandro; Visco, Emanuele; Branca, Luca; et al.
Abstract : Aims: To explore whether left ventricular reverse remodelling (LVRR) is a predictor of outcomes in patients with functional mitral regurgitation (FMR) undergoing MitraClip procedure. Methods and results: We analysed 184 consecutive patients with FMR who underwent successful MitraClip procedure. LVRR was defined as a reduction in left ventricular end‐systolic volume ≥ 10% from baseline to 6 months. LVRR was observed in 79 (42.9%) patients. Compared with non‐LVRR, LVRR patients were more likely to be females, less likely to have an ischaemic aetiology of mitral regurgitation or a prior (<6 months) heart failure (HF) hospitalization, and had smaller left ventricular dimensions. New York Heart Association class improved from baseline up to 1‐year follow‐up in both groups. Higher rates of overall survival (87.3% vs. 75.2%, P = 0.039), freedom from HF hospitalization (77.2% vs. 60%, P = 0.020), and freedom from the composite endpoint (cardiovascular mortality or HF hospitalization) (74.7% vs. 55.2%; P = 0.012) were observed in LVRR vs. non‐LVRR patients at 2‐year follow‐up. LVRR was associated with a significant reduction of the adjusted relative risk of mortality, HF hospitalization and composite endpoint [hazard ratio (HR) 0.44; 95% confidence interval (CI) 0.20–0.96, P = 0.040; HR 0.55; 95% CI 0.32–0.97, P = 0.038; and HR 0.54; 95% CI 0.32–0.92, P = 0.023, respectively]. Female gender, absence of diabetes, freedom from prior HF hospitalization, non‐ischaemic aetiology of mitral regurgitation, and left ventricular end‐diastolic diameter < 75 mm were found to be independent predictors of LVRR. Conclusions: Left ventricular reverse remodelling is associated with better long‐term outcomes in patients with FMR successfully treated with MitraClip. A careful patient selection may be useful as specific baseline features predict favourable left ventricular remodelling. [Correction added on 17 January 2019, after online publication: the preceding sentence has been changed.]